HUMAN RESOURCE MANAGEMENT STRATEGY IN DEALING WITH CRISIS: CASE STUDY OF MASS LAYOFFS AT KFC INDONESIA - Harmen, Hilma; Pandiangan, Raja Satrio; Marpaung, Irvan Aldi Josua; Siagian, Nielsen Samuel Panahatan; Anak Ampun, Grace Febrina Analita; Situmorang, Listem Wisiska; Zahra, Saffanah Alya (Trunojoyo University of Madura, 2024)
The purpose of this study is to find out what mistakes caused mass layoffs that caused workers to lose their jobs and what solution strategies can be applied to reduce this very critical problem in the scope of human resource management. In this study, the method used is a qualitative method that presents descriptive theories that are very relevant to the problem, reinforced with accurate, current data and supported by various literature reviews. The population targeted in the study were employees who were given layoffs that could be caused by management errors in managing the company and causing losses so that they took action in terminating employment with employees en masse. The results of the study are in the form of an analysis of the management of failed companies so that effective strategies must be provided in managing the company in the study of solutions to overcome mass layoffs.